Principal Management To Improve Professional Competence of Tahfidz Teachers in Modern Schools : Manajemen Kepala Sekolah Untuk Meningkatkan Kompetensi Profesional GuruTahfidz di Sekolah Modern - Prasetyo, Ifan Agus; Fauji, Imam (Indonesian Journal of Innovation Studies, 2026)
General Background Professional teacher competence significantly determines instructional quality and learning outcomes in specialized educational programs. Specific Background Modern elementary schools implementing Tahfidz curricula require structured administrative approaches to support instructors in guiding Quranic memorization. Knowledge Gap However, empirical investigation into managerial strategies executed within high-profile urban modern primary schools remains sparse. Aims This study analyzes principal management across planning, organizing, executing, and evaluating dimensions to improve Tahfidz teacher competence at SD Al Falah Surabaya. Results Findings show structured leadership—encompassing technology workshops, mentoring, and continuous performance supervision—effectively elevates teaching proficiency, despite challenges like specialized training scarcity and implementation inconsistency. Novelty This work establishes an empirical management model combining technological integration with structured Quranic pedagogical development in private modern primary education. Implications Educational leaders can utilize these findings to structure flexible training programs and continuous monitoring systems tailored for specialized religious educators. Key Findings Highlights Systematic planning and ongoing supervisory evaluation directly elevate specialized pedagogical execution in Quranic memorization programs. Major operational barriers include scarce tailored training sessions, tight teaching schedules, and inconsistent post-training classroom implementation. Integrating digital instructional tools alongside professional mentoring offers a viable framework for modernizing elementary Quranic education. Keywords: Principal Management, Professional Competence, Quranic Educators, Modern Primary School, Educational Leadership